Risk Tolerance, Impulsivity, and Self-esteem: Differences and Similarities between Gamblers and Non-Gamblers in a Pilot Study - Suen, Victoria; Brown, Matthew R.G.; Morck, Randall K.; Cribben, Ivor; Silverstone, Peter H. (Advances in Social Sciences Research Journal, 2017)
Risk-taking ranges from socially beneficial entrepreneurship through games of chance as entertainment to problem gambling that can be both individually and socially destructive. There are many conflicting theories about what leads individuals to become gamblers, although some consensus suggests a link to personality traits. Links between gambling and impulsivity, risk tolerance and self-esteem remain unclear, and childhood experiences may be pertinent. To explore these issues, we studied 41 non-gamblers and compared them to 16 individuals identified as frequent gamblers in which both groups completed a psychological battery. The study goal was to try and determine which measures best relate to high propensities towards gambling, particularly with regards to different domains of risk tolerance. In this small sample, the results show the gamblers to have statistically significantly greater financial, recreational and social risk tolerance, as well as higher impulsivity and more favorable attitudes towards gambling overall. In contrast, there were no statistically significant differences in self-esteem and adverse childhood experiences. Multivariate models reveal three measures of risk tolerance to significantly contribute to gambling propensity. While differences in impulsivity exist to some degree, those for self-esteem and adverse childhood experiences were less important. This preliminary research suggests that risk tolerance may be a key psychological determinant in gamblers, but this relatively small study does not support previous suggestions that impulsivity, low self-esteem, or adverse childhood experiences are as important. Repeated studies with larger samples may help further clarify these findings